Rice marketing system, profitability and middlemen’s role in two districts of Bangladesh: Rice marketing system in Bangladesh (Journal of the Bangladesh Agricultural University, 2019)
The study attempts to identify the rice marketing channels, market actors and their marketing functions in Bogura and Gaibandha districts in Bangladesh. The paper also examines the rice marketing cost and margin and highlight major obstacles of market actors. Primary data were collected from 25 middlemen by using pretested semi-structured interview schedule in 2017. Rice millers, wholesalers and retailers were the major market’s actors in the study areas. Most of the rice millers buy paddy directly from the farmers by using their agent. After processing rice, rice millers sell rice to the wholesalers, and retailers. Rice millers marketing costs were higher in the Bogura district (Tk.569.8/40kg) than Gaibandha district (Tk.526.0/40kg). However, retailers’ marketing costs were higher in Gaibandha district (Tk.43.0/40kg) than Bogura district (Tk.39.1/40kg). Among all intermediaries, marketing margins was highest for rice millers which were Tk. 227.5/40kg. Middlemen have no sufficient capital for investment. Therefore, Government, Non Government Organizations and other institutional credit should be available to them at the reasonable interest rate.J Bangladesh Agril Univ 17(4): 567–573, 2019